(untitled) (Revista Brasileira Multidisciplinar, 2024)
This article is the result of research carried out with farmers affiliated to the Association of Rural Producers of the Community of the Piancó Hydrographic Basin, Goiás, Brazil, and aims to present the socioeconomic profile and the relationship of the use of agrochemicals with the illness process of the research participants. The research was exploratory and qualitative approach. The instruments used for data collection were oral reports and field observations. The research revealed that the average contact time of farmers with agrochemicals is approximately 23 years; The application of agrochemicals is done through manual and mechanical costal bombs; Personal protective equipment is used inadequately; The most widely used pesticide is the herbicide glyphosate. It was found that most surveyed farmers come into contact with pesticides twice a week and do not relate them to health problems and intoxication. However, respondents who were exposed for a long time to pesticides reported cases of cancer, pleural spill and pneumonia. The result of the research allows reflection on the contradictions in the use of pesticides and the need to sensitize farmers about this scenario, through environmental education, health education practices and the strengthening of agroecology.